Legionella detection from clinical and environmental samples (Italian Journal of Public Health, 2004)
Several methods are used for diagnosis of legionellosis: culture, urinary antigen detection, serologic tests, PCR etc., characterised by different level of specificity, sensitivity and rapidity. Microbiological diagnosis is an essential tool to for the prompt adoption of an adequate antimicrobial therapy and to understand the real diffusion of legionellosis.Likewise, the environmental samples analysis allows us to know the distribution of the Legionella in the environment and to detect the origin of the infection during an outbreak by comparing clinical and environmental strains.